Creative Ways of Knowing in Engineering - Bairaktarova, Diana; Eodice, Michele (Springer International Publishing : Imprint: Springer, 2017)
This book offers a platform for engineering educators who are interested in implementing a "creative ways of knowing" approach to presenting engineering concepts. The case studies in this book reveal how students learn through creative engagement that includes not only design and build activities, but also creative presentations of learning, such as composing songs, writing poems and short stories, painting and drawing, as well as designing animations and comics. Any engineering educator will find common ground with the authors, who are all experienced engineering and liberal arts professors, who have taken the step to include creative activities and outlets for students learning engineering. • Demonstrates various methods for returning to the basics of engineering education, which include design and creativity, teamwork and interdisciplinary thinking; • Discusses a timely topic, as higher education puts more attention on the student experience of learning in all disciplines; • Includes actual student products demonstrating "creative ways of knowing in engineering"; • Highlights multiple ways to teach engineering concepts.